SEARCHING THE GAMMA-RAY SKY FOR COUNTERPARTS TO GRAVITATIONAL WAVE SOURCES: FERMI GAMMA-RAY BURST MONITOR. AND LARGE AREA TELESCOPE OBSERVATIONS OF LVT151012 AND GW151226 - Racusin, J. L.; Burns, E.; Goldstein, A.; Connaughton, V.; Wilson-Hodge, C. A.; Jenke, P.; Blackburn, L.; Briggs, M. S.; Broida, J.; Camp, J.; Christensen, Nelson; Hui, C. M.; et al. (Astrophysical Journal, 2017)
We present the Fermi Gamma-ray Burst Monitor (GBM) and Large Area Telescope (LAT) observations of the LIGO binary black hole merger event GW151226 and candidate LVT151012. At the time of the LIGO triggers on LVT151012 and GW151226, GBM was observing 68% and 83% of the localization regions, and LAT was observing 47% and 32%, respectively. No candidate electromagnetic counterparts were detected by either the GBM or LAT. We present a detailed analysis of the GBM and LAT data over a range of timescales from seconds to years, using automated pipelines and new techniques for characterizing the flux upper bounds across large areas of the sky. Due to the partial GBM and LAT coverage of the large LIGO localization regions at the trigger times for both events, differences in source distances and masses, as well as the uncertain degree to which emission from these sources could be beamed, these non-detections cannot be used to constrain the variety of theoretical models recently applied to explain the candidate GBM counterpart to GW150914.
CRIS-Team WoS Importer:2020-01-15